2001
DOI: 10.1046/j.1464-410x.2001.02149.x
|View full text |Cite
|
Sign up to set email alerts
|

A single‐centre experience of retroperitoneoscopy using the balloon technique

Abstract: Objective To report the experience in one centre of the efficacy and safety of retroperitoneal laparoscopic procedures (RLPs procedures (90.6%). The operative duration was 0.5-5.5 h, depending on the difficulty of the procedure and the presence or absence of adhesions. The overall incidence of complications was 12.9%, but decreased to 9% for the last 100 procedures. There were only five major complications, e.g. avulsion of the ureter, torn renal pelvis, colonic injury and severe hypotension, but none were rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…Although our series seems small (30 cases), it is still the third largest series which has ever been reported in the world literature 9,10 …”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Although our series seems small (30 cases), it is still the third largest series which has ever been reported in the world literature 9,10 …”
Section: Discussionmentioning
confidence: 75%
“…However, we preferred to perform through the retroperitoneal route. The retroperitoneal approach has several advantages over the transperitoneal approach, such as no need to mobilize the colon, and a low risk of visceral organ injury 5,10 . In addition, postoperative urinary leakage does not interfere with the peritoneal cavity 5,10 .…”
Section: Discussionmentioning
confidence: 99%
“…The retroperitoneal route has several advantages over the transperitoneal approach: the risk of visceral injury is low, abdominal adherences and pain from peritoneal irritation do not interfere with the procedure, and there is no need to mobilize the colon [3,12]. The main disadvantage of retroperitoneoscopy is the small surgical field which needs to be expanded to create a viable working area.…”
Section: Discussionmentioning
confidence: 99%
“…All these balloon devices are equally effective in creating a retroperitoneal space but the homemade balloon devices have a high incidence of rupture. Though occasional complications due to extraperitoneal balloon in¯ation have been reported in the past, a recent study showed that if proper precautions are taken, balloon dilatation is quite safe [13][14].…”
Section: Discussionmentioning
confidence: 99%